Antieigenvalue Analysis : With Applications to Numerical Analysis, Wavelets, Statistics, Quantum Mechanics, Finance and Optimization. - Gustafson, Karl E. (World Scientific, 2011)
Karl Gustafson is the creater of the theory of antieigenvalue analysis. Its applications spread through fields as diverse as numerical analysis, wavelets, statistics, quantum mechanics, and finance. Antieigenvalue analysis, with its operator trigonometry, is a unifying language which enables new and deeper geometrical understanding of essentially every result in operator theory and matrix theory, together with their applications. This book will open up its methods to a wide range of specialists.